Intellectual property rights as a challenge to providing global public goods: the cases of public health, food security and climate stability - Clara Brandi; Christine Ladenburger; Anna Pegels (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
Most of the production of new knowledge takes place in developed countries. Some of this knowledge contributes to the provision of global public goods: Knowledge of new medicines helps combat the spread of diseases, modified seeds contribute to food security and clean technologies help mitigate climate change. This highlights the particular need for mechanisms to optimize the balance between the production of this kind of knowledge and its use and diffusion. This paper aims to assess the effect of the TRIPS agreement as the central international agreement for the protection of intellectual property on the provision of three selected global public goods. In the context of health, IPRs may hinder access to affordable medicines for poor people. In the context of food security, they may raise the prices of improved seeds, block follow-on research and hinder seed-saving. In securing climate stability, they may raise the prices of clean technologies such as renewable energies, therewith blocking the diffusion to developing countries and constraining their ability to reduce greenhouse gas emissions. However, IPRs may also foster innovation. The paper concludes by comparing the three areas of global public goods provision and deriving policy recommendations for each area.
Keywords: 330